Burza nad Lwowem : reportaz z lat wojennych 1939-1945 we Lwowie ; Kartki z pamietnika - Mekarska-Kozlowska, Barbara; Mekarska-Kozlowska, Barbara (Londyn : Polska Fundacja Kulturalna, 1992)
A personal account of a young girl living in Lwow during the Nazi and Soviet occupation during WW II.
Keywords: Mekarska-Kozlowska, Barbara; World War, 1939-1945 -- Personal narratives, Polish; World War, 1939-1945 -- Ukraine -- Lviv